TINDAK PIDANA PENGANIAYAAN MENGAKIBATKAN KEMATIAN KARENA BELA PAKSA (Putusan No. 103/Pid.B/2021/PN.Gdt): The Crime of Assault Resulting in Death Due to Self-Defense (Judgment No. 103/Pid.B/2021/PN.Gdt) - Abraham Julian Hasudungan; Rini Purwaningsih (AMICUS CURIAE, 2025)
In the context of persecution, there is a criminal law principle called self-defense that exceeds the limit, also called Noodweer Exces. The problem of this study is how the regulations regarding ordinary self-defense and those that exceed the limit based on decision number 103/Pid.B/2021/PN.Gdt and whether the consistency of the elements contained in Article 49 Paragraph 2 of the Criminal Code for the case of Noodweer Excesses that occurred in the facts of the trial from decision number 103/Pid.B/2021/PN.Gdt. This study uses a normative type with a descriptive nature, where data is collected through literature studies, with legal sources used including the 1945 Constitution, Article 49 of the Criminal Code.. This study concludes that the judge's decision decided that Nuryadin was proven guilty of his actions but received a pardon because he had been proven to have committed self-defense that exceeded the limit by the elements listed in Article 49 of the Criminal Code. Taking into account the elements in Article 49 Paragraph 2 of the Criminal Code, Nuryadin is considered to have committed an act of Noodweer Exces by admitting that his actions were an effort to defend himself that exceeded the limits in an emergency.